Challenges and opportunities in the Nigerian economy - Mailafiya, Obed.; National Institute for Policy and Strategic Studies (Nigeria) (Kuru, Nigeria: National Institute for Policy and Strategic Studies, 1989)
This book is the outcome of a workshop organised by the National Institute for Policy and Strategic Studies, Kuru, Nigeria, Dec. 1988. It was focused on entrepreneurship and self-employment for graduates. Papers presented covered the following areas: investment opportunities in agriculture, raw materials, petrochemicals etc.; opportunities and challenges of structural adjustment; the entrepreneurial challenge; the unemployment challenge; how to set up and manage a business; how to prepare a feasibility report and the challenge of leadership in the private sector.
Results of a workshop held in the National Institute for Policy and Strategic Studies, Kuru, Nigeria, Dec. 1988.
Includes bibliographical references.
lje 1/08/1
Loans
Keywords: New business enterprises; Industries; Economic development; Economic conditions; Nigeria